Two Strategies for Europe: De Gaulle, the United States, and the Atlantic Alliance - Bozo, Frédéric; Emanuel, Susan (Rowman & Littlefield Publishers, 2002)
This timely book explores the often stormy French-U.S. relationship and the evolution of the Atlantic Alliance under the presidency of Charles de Gaulle (1958D1969). The first work on this subject to draw on previously inaccessible material from U.S. and French archives, the study offers a comprehensive analysis of Gaullist policies toward NATO and the United States during the 1960s, a period that reached its apogee with de GaulleOs dramatic decision in 1966 to withdraw from NATOOs integrated military arm. This launched the French policy of autonomy within NATO, which has since been adapted without having been abandoned. De GaulleOs policy often has been caricatured by admirers and detractors alike as an expression of nationalism or anti-Americanism. Yet Frederic Bozo argues that although it did reflect the GeneralOs quest for grandeur, it also, and perhaps more important, stemmed from a genuine strategy designed to build an independent Europe and to help overcome the system of blocs. Indeed, the author contends, de GaulleOs actions forced NATO to adapt to new strategic realities. Retracing the different phases of de GaulleOs policies, Bozo provides valuable insight into current French approaches to foreign and security policy, including the recent attempt by President Chirac to redefine and normalize the France-NATO relationship. As the author shows, de GaulleOs legacy remains vigorous as France grapples with European integration, a new role within a reformed NATO, and relations with the United States.